2018
DOI: 10.1002/jcb.28318
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid inhibits osteosarcoma carcinogenesis via suppressing the STAT3/Snail pathway

Abstract: Chlorogenic acid (CA) is a polyphenol compound that possesses anticancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
(60 reference statements)
2
17
0
Order By: Relevance
“…Our findings indicate that CGA inhibits cell viability, cell growth, and colony-forming ability in all osteosarcoma cell lines tested, with a different sensitivity among them (U2OS and MG-63 the most and the least sensitive, respectively). Notably, our data are fully in agreement with a very recent study in which CGA exerts antiproliferative effects in p53-deficient OS cells Saos-2 and MG-63 (F. Zhang, Yin, Han, Jiang, & Bao, 2018). Herein, we confirm and extend such data, providing the first evidence regarding CGA and p53-proficient U2OS cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings indicate that CGA inhibits cell viability, cell growth, and colony-forming ability in all osteosarcoma cell lines tested, with a different sensitivity among them (U2OS and MG-63 the most and the least sensitive, respectively). Notably, our data are fully in agreement with a very recent study in which CGA exerts antiproliferative effects in p53-deficient OS cells Saos-2 and MG-63 (F. Zhang, Yin, Han, Jiang, & Bao, 2018). Herein, we confirm and extend such data, providing the first evidence regarding CGA and p53-proficient U2OS cells.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to ERK1/2 tendency, CGA induces a significant downregulation of STAT3 phosphorylation after 48 hr of treatment, whereas no obvious variations have been detected in the STAT3 total protein levels. Importantly, these findings are in line with a very recent paper in which the importance of STAT3 in CGA-produced outcome is described (F. Zhang et al, 2018). In particular, they show that CGA downregulates phospho-STAT3 in MG-63 and Saos-2 cells and that the activation of the STAT3/Snail pathway reverts the effects of CGA on OS cell growth and apoptosis.…”
Section: Discussionsupporting
confidence: 90%
“…Matrix metallopeptidases (MMPs) are known to play important roles in breast cancer metastasis. A wellstudied mechanism of STAT3-mediated cell metastasis is through upregulating MMP2, MMP9, Twist, Snail, Slug and vimentin [47][48][49]. Ma et al have reported that inhibition of STAT3 phosphorylation could reduce the expression of vasodilator-stimulated phosphoprotein (VASP), MMP2 and MMP9 in breast cancer [50].…”
Section: The Role Of Stat3 In Breast Cancer Metastasismentioning
confidence: 99%
“…Since both compounds have been reported to induce cell death in OS, we speculated that combination treatment CGA plus Doxo could enhance single-agent cytotoxicity [23,24,34]. To address this hypothesis, we firstly discriminated living from dead cells using Trypan Blue as the exclusion dye.…”
Section: Cga Enhances Doxo-mediated Cytotoxic Effects In Os Cellsmentioning
confidence: 99%
“…In this connection, we lastly examined the CGA consequences in three different human OS cell lines, demonstrating that, albeit to a different extent, CGA inhibits growth and promotes cell death via apoptosis induction [23]. Moreover, CGA prevented Tyr705 Signal Transducer and Activator of Transcription 3 (STAT3) phosphorylation and triggered a remarkable Extracellular-signal-Regulated Kinase1/2 (ERK1/2) activation [23,24].…”
Section: Introductionmentioning
confidence: 99%